Analysis of Science Literacy Ability of 8th Grade Students in Junior High School - Amantha, Sacherly; Sartika, Septi Budi (Science Education and Application Journal, 2025)
Analysis of Science Literacy Ability of 8th Grade Students in Junior High School. This study aims to determine the scientific literacy skills of 8th-grade students at SMP Cendekia Sidoarjo. This research is a non-experimental quantitative study using a survey method and descriptive statistical analysis techniques. The population and sample of this study consisted of 90 students, selected from the entire 8th-grade population at SMP Cendekia Sidoarjo. Data collection was carried out using an instrument consisting of a scientific literacy test with 18 questions based on scientific literacy indicators. The students' abilities were classified into achievement categories: very good, good, sufficient, poor, and very poor. The results indicate that the average scientific literacy ability of students falls into the sufficient category, with 75% on indicator 3, 67% on indicator 5, 72% on indicator 4, 64% on indicator 6, and 67% on indicator 9. Meanwhile, the poor and very poor categories are observed in indicator 7 (55%), indicator 1 (36%), indicator 2 (51%), and indicator 8 (53%). The study concludes that low scientific literacy skills can be influenced by various factors, including students' low reading interest, assessment tools that do not focus on developing scientific literacy, and the lack of practice in solving problems with PISA-style characteristics. Additionally, factors such as students' backgrounds, interests, study intensity, and attitudes toward science also contribute to the low scientific literacy achievements of students in Indonesia.